Parents' perspective on probiotics in preschool children: A cross-sectional survey - Bezek Katja; Fajković Emina; Stubelj Mojca (Sciendo, 2023)
The composition of the human gut microbiota, which can also be regulated by the consumption of probiotics, has a significant impact on host health. The main source of probiotics can be foods such as fermented foods, yogurts, fermented drinks and/or probiotic supplements. While parents play a critical role in ensuring the well-being of their children, this cross-sectional study is focused on parents' perspectives regarding the use of probiotics in the preschool period.